Relationship of contact angle of spray solution on leaf surfaces with weed control - Renata Thaysa da Silva Santos (Nature Portfolio, 2021)
Abstract The weeds are important in agricultural and livestock areas because these plants can cause several damages, especially in the yield. The herbicide pulverization for weed control is the most used, but the efficiency of the control can be dependent the several factors, for example, the correct chose the herbicide and the mixture or not with adjuvant. This study aimed to evaluate the contact angle of herbicide solution droplets associated with adjuvant when deposited on the leaf surface of different weed species and their relationship with chemical control. For the contact angle experiment, the design was completely randomized, with four repetitions, while for the control experiment, a randomized block design was used, both experiments were arranged in a factorial (4 × 2 + 1) design. Factor A corresponded to four spray solutions containing the herbicide no addition of adjuvants and herbicide associated with adjuvants (vegetable oil, mineral oil, and lecithin), factor B to two herbicide dosages, and additional treatment corresponded to water. The contact angle was determined in six weed species: Crotalaria incana, Lantana camara, Ipomoea grandifolia, Asclepias curassavica, Sida obtusifolia, and Ricinus communis, on the adaxial and abaxial surface of each species, and an artificial surface. For the weed control experiment was used two weed species: C. incana and L. camara. The multivariate analysis allowed the understanding of the behavior of the contact angle of the different groups on the natural and artificial surfaces, due to the formation of factors. For all plants, except for the abaxial surface of I. grandifolia and the adaxial surface of A. curassavica, the association of herbicide and adjuvants reduced contact angle on the surfaces. The chemical control resulted in an indirect relation with contact angle, where smaller contact angles of the herbicide solution resulted in a higher percentage of plant intoxication. Therefore, for this situation, it is recommended to use the herbicide aminopyralid + fluroxypir associated with lecithin.